Tackling wicked problems in infection prevention and control: a guideline for co-creation with stakeholders - van Woezik, Anne F. G. (Antimicrob Resist Infect Control, 2016)
BACKGROUND: Infection prevention and control can be seen as a wicked public health problem as there is no consensus regarding problem definition and solution, multiple stakeholders with different needs and values are involved, and there is no clear end-point of the problem-solving process. Co-creation with stakeholders has been proposed as a suitable strategy to tackle wicked problems, yet little information and no clear step-by-step guide exist on how to do this. The objectives of this study were to develop a guideline to assist developers in tackling wicked problems using co-creation with stakeholders, and to apply this guideline to practice with an example case in the field of infection prevention and control. METHODS: A mixed-method approach consisting of the integration of both quantitative and qualitative research was used. Relevant stakeholders from the veterinary, human health, and public health sectors were identified using a literature scan, expert recommendations, and snowball sampling. The stakeholder salience approach was used to select key stakeholders based on 3 attributes: power, legitimacy, and urgency. Key values of stakeholders (N = 20) were derived by qualitative semi-structured interviews and quantitatively weighted and prioritized using an online survey. RESULTS: Our method showed that stakeholder identification and analysis are prerequisites for understanding the complex stakeholder network that characterizes wicked problems. A total of 73 stakeholders were identified of which 36 were selected as potential key stakeholders, and only one was seen as a definite stakeholder. In addition, deriving key stakeholder values is a necessity to gain insights into different problem definitions, solutions and needs stakeholders have regarding the wicked problem. Based on the methods used, we developed a step-by-step guideline for co-creation with stakeholders when tackling wicked problems. CONCLUSIONS: The mixed-methods guideline presented here provides a systematic, transparent method to identify, analyze, and co-create with stakeholders, and to recognize and prioritize their values, problem definitions, and solutions in the context of wicked problems. This guideline consists of a general framework and although it was applied in an eHealth context, may be relevant outside of eHealth as well.